Florida's Citrus Canker Eradication Program (CCEP): Benefit-Cost Analysis - Marisa L. Zansler; Thomas H. Spreen; Ronald P. Muraro (EDIS)
In this paper, an economic analysis of the Citrus Canker Eradication Program (CCEP) on the Florida citrus industry is conducted through employment of a benefit-cost analysis of retaining the current policy. A benefit-cost analysis of the CCEP in Florida is developed using the predicted values of the benefits and the costs associated with the policy. The actual expenditures of implementation to-date are weighed against the estimated loss of revenue and the cost savings associated with an industry with pervasive citrus canker in an attempt to assess the net benefits of the policy. This is EDIS document FE531, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published March 2005.